2002
DOI: 10.1002/j.2050-0416.2002.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Mashing Studies with Unmalted Sorghum and Malted Barley

Abstract: The effects on wort quality when mashing with unmalted sorghum (0-100%) and malted barley (100-0%) in combination with industrial enzymes were evaluated. A mashing program with temperature stands at 50°C, 95°C and 60°C was used. Different combinations of commercial enzymes were evaluated. A heat stable a-amylase was found to be essential for efficient saccharification. The inclusion of a fungal ␣-amylase in mashes with a high sorghum content improved filtration rates to that of 100% malted barley mashes. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Goode et al 22 , found that, when using optimised mashing conditions acceptable worts could be produced from a grist of 100% unmalted sorghum when optimised levels of a heat stable ␣-amylase, fungal ␣-amylase and a bacterial protease were incorporated into the system. Goode et al 21 , also found the mashing program suitable when brewing with Nigerian white unmalted sorghum (Fara Fara variety) as adjunct to various proportions of malted barley.…”
Section: -2863(9'8-32mentioning
confidence: 97%
See 3 more Smart Citations
“…Goode et al 22 , found that, when using optimised mashing conditions acceptable worts could be produced from a grist of 100% unmalted sorghum when optimised levels of a heat stable ␣-amylase, fungal ␣-amylase and a bacterial protease were incorporated into the system. Goode et al 21 , also found the mashing program suitable when brewing with Nigerian white unmalted sorghum (Fara Fara variety) as adjunct to various proportions of malted barley.…”
Section: -2863(9'8-32mentioning
confidence: 97%
“…More recent comprehensive reviews on brewing lager beer from sorghum, particularly, malted sorghum have been compiled by Agu and Palmer 2 and Owuama 38 . Due to problems associated with malted sorghum such as the development of insufficient diastatic power, limited protein modification, high malting costs, high malting losses, together with the need to supplement mashes with exogenous enzymes, it could seem more feasible to mash with unmalted grains and commercial enzymes 3,4,8,14,21,22,30,31 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
See 2 more Smart Citations
“…This is indeed one of the major problems encountered in mashing with some malted sorghum cultivars [3][4][5]8,9,13,14,17,18,21 . However, it is known that acceptable worts for beer brewing can be obtained from 100% unmalted sorghum by supplementing the mashes with optimal amounts of thermostable α-amylase, fungal α-amylase and bacterial proteases 11 . In contrast, what is not known is the effect of singular or combined contributions of these enzymes on starch liquefaction of unmalted sorghum grains.…”
Section: Introductionmentioning
confidence: 99%